A Heart’s Pledge in Metaerotopoetics - Horváth, Imre Olivér (Hungarian Journal of English and American Studies, 2020)
Book review:Gray, Erik. The Art of Love Poetry. Oxford: Oxford UP, 2018. 210 pages. ISBN 978-0-19-875297-4. Hb. £50.00.